2008
DOI: 10.3201/eid1402.070889
|View full text |Cite
|
Sign up to set email alerts
|

Greek Goat Encephalitis Virus Strain Isolated fromIxodes ricinus,Greece

Abstract: A strain of Greek goat encephaltitis virus was isolated from engorged Ixodes ricinus ticks that had fed on goats in northern Greece. The strain was almost identical to the prototype strain isolated 35 years ago.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 17 publications
(7 citation statements)
references
References 10 publications
0
7
0
Order By: Relevance
“…Further north, it occurs up to 1450 m.a.s.l in Switzerland [34], 1560 m.a.s.l in Austria [38], 1080–1270 m.a.s.l in Czech Republic [30] and 700 m.a.s.l in Scotland, UK [39]. At the other extreme, in arid parts of Europe typical of the Mediterranean, for example in Greece, no I. ricinus ticks have been found below 600 m.a.s.l [40]. Of the ticks removed from humans in Greece during June-September 2008 in areas of low altitude, only 1% (5/519) were I. ricinus [41].…”
Section: Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…Further north, it occurs up to 1450 m.a.s.l in Switzerland [34], 1560 m.a.s.l in Austria [38], 1080–1270 m.a.s.l in Czech Republic [30] and 700 m.a.s.l in Scotland, UK [39]. At the other extreme, in arid parts of Europe typical of the Mediterranean, for example in Greece, no I. ricinus ticks have been found below 600 m.a.s.l [40]. Of the ticks removed from humans in Greece during June-September 2008 in areas of low altitude, only 1% (5/519) were I. ricinus [41].…”
Section: Reviewmentioning
confidence: 99%
“…In more arid parts of Europe, around the Mediterranean, humidity is a controlling factor in the distribution of I. ricinus , exemplified by studies in Greece that report a lower altitudinal limit of 600 m.a.s.l. [40,41]. …”
Section: Reviewmentioning
confidence: 99%
“…There are a number of closely related tick-borne viruses that cause neurological disease in sheep or goats, however, which have been described as louping ill-like viruses (Gao et al , 1997). These have included Turkish sheep encephalitis virus (Gao et al , 1993b; Whitby et al , 1993), Greek goat encephalitis virus (Papa et al , 2008) and Spanish sheep encephalitis virus (Marin et al , 1995). There remains some debate over the optimum classification of the different isolates of LIV and the LIV-like viruses within the tick-borne encephalitis complex (Gao et al , 1997; Norberg et al , 2013).…”
Section: Molecular Epidemiologymentioning
confidence: 99%
“…A survey conducted in Northern Greece showed that 2.06% among 921 apparently healthy individuals had IgG antibodies to TBEV, while none of 302 patients with central nervous system (CNS) infection was found to have been infected by TBEV [Pavlidou et al, 2007]. Instead, two strains of Greek goat encephalitis virus (GGEV), which is related closely to TBEV, have been isolated in Greece [Papadopoulos et al, 1971; Papa et al, 2008]. It has been suggested that the observed seroprevalence is probably due to cross‐reactivity to GGEV [Pavlidou et al, 2008].…”
Section: Introductionmentioning
confidence: 99%